Does English proficiency impact on health outcomes for inpatients undergoing stroke rehabilitation? - Davies, S.; Dodd, K.; Tu, A.; Zucchi, E.; Zen, S.; Hill, Keith (2015)
Purpose: To determine whether English proficiency and/or the frequency of interpreter use impacts on health outcomes for inpatient stroke rehabilitation. Method: Study design: Retrospective case–control study. Participants: People admitted for inpatient stroke rehabilitation. A high English proficiency group comprised people with native or near native English proficiency (n?=?80), and a low English proficiency group comprised people who preferred a language other than English (n?=?80). Outcome measures: Length of stay (LOS), discharge destination and Functional Independence Measure (FIM). Results: The low English proficiency group showed a greater improvement in FIM from admission to discharge (p?=?0.04). No significant differences were found between groups in LOS, discharge destination and number of encounters with allied health professionals. Increased interpreter usage improved FIM efficiency but did not significantly alter other outcomes. Conclusion: English proficiency does not appear to impact on health outcomes in inpatient rehabilitation with a primarily in-house professional interpreter service. However, there is a need for a larger powered study to confirm these findings.Implications for rehabilitationPeople with low English proficiency undergoing inpatient stroke rehabilitation in a setting with a primarily in-house professional interpreter service, achieved similar outcomes to those with high English proficiency irrespective of frequency of interpreter usage.A non-significant increase of 4 days length of stay was observed in the low English proficiency group compared to the high English proficiency group.For patients with low English proficiency, greater change in Functional Independence Measure efficiency scores was observed for those with higher levels of interpreter use relative to those with low interpreter use. Clinicians should optimise use of interpreters with patients with low English proficiency when possible.